Mauritius : Technical Assistance Report-Strengthening Bank Resolution and Crisis Management Framework. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses measures needed to strengthen bank resolution and crisis management framework in Mauritius. The current legal framework in Mauritius does not provide the supervisor with adequate triggers and powers to mitigate risks at a sufficiently early stage. The law should provide for a broader range of corrective tools that allow the supervisor to restore weak banks to sound financial conditions. A new resolution framework is needed to effectively manage failing banks, safeguard financial stability as well as limit moral hazard. Formal plans describing how the resolution authority will manage the failure of individual banks and their groups need to be developed.